Pengaruh Penggunaan Medial Arch Support Terhadap Sudut Valgus Ankle Pada Kondisi Flatfoot - Agus Setyo Nugroho; Prasetyo Catur Utomo; Dewanti Nuraini (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Medial Arch Support, Valgus Ankle, Flat Foot. The purpose of this study was to determine the effect of medial arch support on the angle of valgus ankle in flat foot condition. The type of this research is ExperimentCross SectionalQuasi with one group Pre Pre and Post Test Design. In order to determine the effect of medial arch support on the angle of valgus ankle on the condition of flatfoot of children aged 10 to 12 years, the instruments, materials or tools in this study consist of (1) medialarch supportsize small (20, 22, 23) (2) goniometer (3) Stationery (4) Resulting Sheet (5)Footprint Frame. The results of the study found that there is an effect of decreasing the degree of ankle valgus in flat foot conditions. Pre post Test The left leg before and after treatment showed p = 0.000 (p <0.05). And result of pre foot test data of right foot before and after treatment showed p = 0.000 (p <0,05). From this data it can be concluded that there is influence of medial arch support to angle valgus ankle at flat foot condition.